Using Teaching Excellence Surveys to Evaluate Improvements in Teaching Confidence - Howe, Erica E; Kalender-Rich, Jessica L; Brimacombe, Michael; Polsak, Micholee; Lowry, Becky; Vansaghi, Lisa (Kansas Journal of Medicine, 2015)
BACKGROUND: There are many surveys to assess teaching excellence, but few validated tools to assess improvements in teaching confidence among faculty over time. We hypothesized that previously validated surveys for learner evaluation of faculty teaching excellence also can be used as a self-evaluation tool to assess changes in faculty teaching skills confidence over time. METHODS: A cohort study was designed using a composite survey from two previously validated surveys (SETQ and CanMEDS) on teaching excellence. The composite survey was administered before and after a faculty development course on teaching excellence at the University of Kansas Medical Center in the Spring of 2012. Course “completers” attended more than 50% of the course and “non-completers” attended 50% or less of the course. RESULTS: The overall mean change in survey result scores on a five-point Likert scale was nearly one point for “completers” (mean difference = 0.92, SD = 0.41) as opposed to 0.34 for “non-completers” (SD = 0.34, p = 0.001). The Cronbach’s alpha coefficients for the pre-course surveys were 0.83 and 0.85 versus 0.88 and 0.83 for the post-course surveys, indicating a high internal consistency for both survey instruments. CONCLUSIONS: Measurable improvements in teaching skills confidence occur following faculty professional development courses. These improvements can be assessed more efficiently by using previously validated and reliable assessment tools in new and innovative ways.